A broadband slant polarized cavity backed microstrip‐fed wide‐slot antenna array. Issue 5 (9th February 2020) - Zarifi, Davoud; Ahmadi, Ali
Abstract: This article deals with the design of a broadband cavity‐backed microstrip‐fed wide‐slot antenna array for L‐band applications. For verification purpose, a sample 1 × 4‐element antenna array has been designed, manufactured and tested. Experimental results have shown satisfactory agreement with the simulation. The proposed antenna array exhibits a measured impedance bandwidth of 1.4 GHz (90%) with frequency of 0.85 to 2.25 GHz and the gain is higher than 11 dBi. The designed antenna has small size and low weight and can be fabricated using a low‐cost fabrication process for easy integration with RF circuits and microwave components. This work is useful for some radar applications and radio frequency identification systems.